Peningkatan Kemampuan Membaca Melalui Pembelajaran Kooperatif Learning type Jigsaw Pada Murid Kelas VI SD Inpres Bertingkat Sungguminasa Kabupaten Gowa - Desy Ayu Andhira (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This classroom action research aims to improve reading skills through Jigsaw type cooperative learning for class VI students at SD Inpres, Sungguminasa, Gowa Regency. The subjects of this research were 40 grade VI students at SD Inpres Multilevel Sungguminasa, Gowa Regency. Academic Year 2023/2024. This PTK consists of 2 cycles, each consisting of 3 meetings. Data collection was carried out using the results of students' work when carrying out actions and observation sheets. The collected data was analyzed using quantitative analysis and qualitative analysis. The results achieved were: (1) students' reading ability before the action was held was in the low category with an average score of 4.88 from the highest possible score of 10. (2) Students' reading ability after taking action in the form of Jigsaw type cooperative learning in Cycle I was in the high category with an average score of 8.04 from the highest possible score of 10. (3) Students' reading ability after taking action, in the form of learning by applying models Jigsaw type cooperative learning in Cycle II was in the very high category with an average score of 8.84 from the highest possible score of 10. (4) There was an increase in the percentage of student attendance. (5) Students' interest, attention and motivation in participating in the learning process using the Jigsaw cooperative model has also increased, this can be seen from the increase in student activity in the learning process. The results of this research also show changes on the teacher's side, initially teachers were less creative in using various Jigsaw type cooperative learning strategies, which had a good impact, apparently being able to motivate and increase teacher interest in developing effective learning.